Controlling Role in Collaborative and Consultative Community Participation in Education Implementation of Primary School - Lukman Hakim (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to determine the role of controlling collaborative and consultative community participation in the implementation of education in elementary schools. This study used a qualitative research approach with a survey method. This research was conducted by one of the state Islamic Madrasah in Mataram. Data were collected through observation, documents and questionnaires. Checking the validity of research data in this study used Lincoln and Guba's theory which consisted of 4 steps as follows, 1) credibility, transferability, dependability, and confirmability. The data analysis process was carried out through data reduction, data presentation, and conclusion making stages. The results of the study concluded that the control role of collaborative and consultative community participation in the provision of education in elementary schools was carried out through a process of transparency, accountability and control of financial expenditures. The three aspects of control were carried out in the form of a variety of school program support activities and objective assessments. The results of the study had implications for understanding the concept of community participation control in schools through collaboration and consultation. All activities were carried out jointly and in a structured manner.